Crystallographic, dielectric and optical properties of SrBi2Ta2O9 thin films prepared by the polymeric precursor method - Zanetti, S. M.; Sotilo, VCM; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2002)
Strontium bismuth tantalate thin films were prepared on several substrates (platinized silicon (PvTi/SiO2/Si), n-type (100)-oriented and p-type (111)-oriented silicon wafers, and fused silica) by the solution deposition method. The resin was obtained by the polymeric precursor method, based on the Pechini process, using strontium carbonate, bismuth oxide, and tantalum ethoxide as starting reagents. Characterizations by XRD and SEM were performed for structural and microstructural evaluations. The electrical measurements, carried on the MFM configuration, showed P-r values of 6.24 muC/cm(2) and 31.5 kV/cm for the film annealed at 800 degreesC. The film deposited onto fused silica and treated at 700 degreesC presented around 80 % of transmittance.
Keywords: ferroelectric; thin films; SrBi2Ta2O9; microstructure; chemical method